Integrating Critical Thinking and Digital Literacy into Technology Acceptance for Online Counseling: A PLS-SEM Study among Muslim University Students - Ardi, Zadrian; Ganefri, Ganefri; Putra, Ade Herdian; Hidayat, Hendra; Hidayati, Abna (Islamic Guidance and Counseling Journal, 2026)
The rapid development of digital platforms has transformed the landscape of counseling services in higher education, creating an urgent need to understand their acceptance, especially among Muslim university students in Indonesia. This study aimed to examine the influence of critical thinking and academic performance on technology acceptance in online counseling, with a focus on the mediating role of digital literacy. Using a quantitative approach, data were collected through purposive random sampling from 815 Muslim university students (49 % male; 51% female) at Universitas Negeri Padang and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study employed validated scales for critical thinking, academic performance, digital literacy, and technology acceptance, all of which showed high reliability (Cronbach’s alpha > 0.90). The findings supported the proposed hypotheses, showing that both critical thinking and academic performance significantly influenced digital literacy and technology acceptance. Digital literacy also acted as a significant mediator linking these variables to technology acceptance, confirming its central role in the model. These results underscore the importance of fostering digital competence and academic readiness in promoting effective adoption of online counseling services. The study highlights the need for culturally sensitive digital interventions that align with the ethical and spiritual values of Muslim university students.